Antimicrobial Effect of Ozone Made by KP Syringe of High-Frequency Ozone Generator - Domagoj Prebeg; Marina Katunarić; Ana Budimir; Božidar Pavelić; Sanja Šegović; Ivica Anić (University of Zagreb. School of Dental Medicine, 2016)
Aim:The aim of this study was to evaluate in vitro the antibacterial effect of ozone on suspension of three different bacteria inoculated in prepared canals of extracted human teeth. Material and methods: Ozone was produced by special KP syringe of high frequency ozone generator Ozonytron (Biozonix, München, Germany) from aspirated atmospheric air by dielectric barrier discharge and applied through the tip of the syringe to the prepared root canal. The microorganisms used were Enterococcus faecalis, Staphylococcus aureus and Staphylococcus epidermidis. Results: However, none of the methods was 100% effective against the three bacterial types in suspension. Application of ozone significantly decreased the absolute count of microorganisms (89.3%), as well as the count of each type of bacteria separately (Staphylococcus aureus 94.0 %; Staphylococcus epidermidis 88.6% and Enterococcus faecalis 79.7%). Ozone generated by KP syringe was statistically more effective compared to NaOCl as positive control, for Staphylococcus aureus and Staphylococcus epidermidis. Conclusion: The absolute count of Enterococcus faecalis was statistically decreased without a statistically significant difference between the tested group and positive control, respectively. Among the three types of bacteria in suspension, KP probe had the lowest antimicrobial effect against Enterococcus faecalis.